Introduction to psychology - Atkinson, Rita L.; Atkinson, Richard C.; Hilgard, Ernest R. (New York : Harcourt Brace Jovanovich, 1953)
Introduces contemporary psychology to the beginning student.
includes reference and index.
Keywords: Psychology